Determinants of the Reinsurance Demand in the United Kingdom General liability Insurance Market, 1985-2010 - Ezhieh, Shirin (2012)
This study examines the effect of solvency risk, underwriting risk, investment incentives and tax management objectives on the reinsurance demand by a sample of UK-based liability insurance companies. In addition, the effects of firm-specific factors including firm size and firm profitability on the reinsurance decision of the sample of UK liability insurance companies is tested. Due to the fact that the demand for reinsurance is measured by the reinsurance claims ratio which should be restricted to the unit interval of zero to one, the sample panel data of 2103 firm/year observations is divided into two separate groups. One group includes the UK liability insurers with reinsurance claims ratios defined on the open interval of zero to one and the other group includes the UK liability insurance firms with reinsurance claims ratios equal to the boundary values of zero and/ or one. In group one, it is observed that underwriting risk and firm size are important determinants of the level of the reinsurance purchased by the UK liability insurance companies. Additionally, it is shown that firm size, firm profitability and solvency risk impact the amount of reinsurance purchased by the UK liability insurers in group two. As it is proved that firm size is an important determinant of the reinsurance demand, it should be investigated why it has opposite impacts on the UK liability insurers’ reinsurance decisions in the two separate groups of this study. It is shown that the sample of UK liability insurers mostly constitutes of large insurance companies which are engaging in reinsurance activities contrary to our prediction as they are providing reinsurance internally through their captives or their subsidiaries. On the other hand, the small to normal sized UK liability insurance companies are engaging in reinsurance activities consistent with our prediction and the smaller ones have higher reinsurance demands. Keywords: Reinsurance Claims Ratio, Reinsurance Demand, Firm Size, Bounded